Buddhism and Caste in India and Sri Lanka - Samuels, Jeffrey (Religion compass, 2007)
This article examines the place of caste in Buddhism in India and Sri Lanka. In addition to suggesting a way of reconciling divergent attitudes toward caste in the Pali canon and several Sanskrit texts, this article explores the role that caste has played in the creation of new monastic lineages in eighteenth-, nineteenth-, and twentieth-century Sri Lanka, as well as its role in monastic patronage and temple building in contemporary Sri Lanka.